Assessing the Potential of the Water Soluble Allelopaths of Marsilea minuta in Rice and Wheat - Tanveer,A. (2015)
To investigate the allelopathic effect of Marsilea minuta against the germination and seedling growths of rice (Oryza sativa) and wheat (Triticum aestivum), germination bioassays were conducted in both Petri dish and soil cultures in laboratory conditions. Rice and wheat seeds were allowed to germinate in a 1, 2, 3, 4, and 5% (w/v) aqueous extract of whole plant and 2, 4, 6, and 8% (w/w) plant residue-incorporated soils of M. minuta. In Petri dish experiments, 5% (w/v) an aqueous extract of M. mimuta showed significantly lower germination percentages (18.8% and 56.3%), root lengths (0.9 and 4.5 cm), shoot lengths (3.3 and 12.4 cm), seedling lengths (4.1 and 25.0 cm), root dry weights (1.4 and 5.6 g), shoot dry weights (1.1 and 9.0 g), seedling biomasses (2.5 and 14.6 g), and seedling vigor indices (77.4 and 957.3) in rice and wheat, respectively. In pot experiments, the M. minuta residue infested soil, with 8% concentration, produced significantly lower germination percentages (25.3 and 37.5%), root lengths (2.7 and 6.1 cm), shoot lengths (6.2 and 16.5 cm), seedling lengths (8.9 and 22.6 cm), root dry weights (2.4 and 5.5 g), shoot dry weights (4.0 and 2.8 g), seedling biomasses (6.4 and 8.3 g), and seedling vigor indices (224.1 and 855.3) in rice and wheat, respectively. The highest phytotoxic action of 5% aqueous whole plant extract of M. minuta against test crops seem to be due to the presence of two potent phenolic compounds, namely p-coumaric acid (2.91 mg L-1) and m-coumaric acid (1.59 mg L-1) as determined by HPLC analysis.